Variations in the esterase activity during the germination period of Jatropha curcas seeds - Subramani, T; Manjunath, K C; Chandrashekharaiah, K S; Ramachandra Swamy, N; Siddalinga Murthy, K R (Journal of Phytology, 2011)
Germination brings out the synthesis or activation of enzymes responsible for the degradation of seeds reserves. Among these enzymes, esterases are involved in the metabolic processes of germination and maturation of plants. They are constitutively expressed in seeds during germination to release the reserve materials for the growing embryo. In the present study, total protein content and esterase activity was monitored in germinating Jatropha curcas seeds. The esterase activity and specific activity observed were 9.07 Ã‚Âµmoles/min/gm and 0.09258 IU/mg, respectively. Electophoretic analysis for esterase activity showed thirteen bands of esterases, among these 8 esterolytic bands were major and remaining were minor bands. The protein content and esterase activity decreased on 2nd, 4th, 5th and 8th day of seed germination and activity increased on 3rd, 6th, 7th day of germination. Similarly esterase activity increased on 7th day and decreased on 8, 9 and 10th day in the shoot tissue.Ã‚Â Ã‚Â